2023
DOI: 10.1021/acsestengg.3c00335
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Electrochemical Fouling Control and Electrode Surface Coverage

Soobin Cho,
Donghoon Kang,
Natalia V. Kirienko
et al.

Abstract: Fouling limits the performance of membrane-based water treatment processes and accounts for up to 25% of the operational expenses of membrane-based water treatment processes. Electrically conductive membranes have been proposed as cheaper and more energy efficient alternatives to reduce and remove fouling. In this study, we investigate the relationship between the surface coverage with an electrode and fouling control levels. We use direct laser scribing for the printing of electrodes with varying surface cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…When both nonoxidative and catalytic oxidative are used consecutively, a small fraction of the fouling is removed while the rest can be taken care of by the catalytic oxidative electrocleaning. Some studies have reported that hydrogen evolution can also contribute to the electrocleaning. , However, in the case of nonoxidative electrocleaning, the cleaning solution is DI water with no electrolyte to facilitate electron transfer. Thus, in DI water, the electrochemical redox reactions are inhibited and the generation of hydrogen gas bubbles is negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When both nonoxidative and catalytic oxidative are used consecutively, a small fraction of the fouling is removed while the rest can be taken care of by the catalytic oxidative electrocleaning. Some studies have reported that hydrogen evolution can also contribute to the electrocleaning. , However, in the case of nonoxidative electrocleaning, the cleaning solution is DI water with no electrolyte to facilitate electron transfer. Thus, in DI water, the electrochemical redox reactions are inhibited and the generation of hydrogen gas bubbles is negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that hydrogen evolution can also contribute to the electrocleaning. 69,70 However, in the case of nonoxidative electrocleaning, the cleaning solution is DI water with no electrolyte to facilitate electron transfer. Thus, in DI water, the electrochemical redox reactions are inhibited and the generation of hydrogen gas bubbles is negligible.…”
Section: Cleaning Mechanismsmentioning
confidence: 99%